Reports and reviews. Clinical laboratory technician articulation assisted by clinical laboratory science program restructuring. - Etynre-Zacher P; Cearlock DM (Clinical Laboratory Science)
OBJECTIVE: To describe the restructuring of a university-based clinical laboratory science (CLS) program which facilitated the articulation of clinical laboratory technicians (CLT). SETTING: Northern Illinois University, a large (24,000 students) state-assisted institution. PRACTICE DESCRIPTION: Baccalaureate CLS program. PRACTICE INNOVATION: Multi-institutional restructuring by university and clinical faculty of a CLS program assisted the development of a model curriculum for articulating CLTs. MAIN OUTCOME MEASUREMENT: Graduates can complete baccalaureate requirements without excessive clinical education duplication. They can successfully complete national certification examinations and find or upgrade employment. RESULTS: The articulating CLT assists with the development of a shortened clinical experience which emphasizes areas of need and provides for the development of new areas of expertise. CONCLUSION: Restructuring increased communication and collaboration between university and clinical faculty and facilitated development of a customized curriculum for articulating students.